Remapping Translation Studies: Towards a Translation Studies Ontology - Vandepitte, Sonia (Meta, 2008)
Abstract Building on a common view of translation as a human intentional activity, this article presents a translation studies thesaurus in which all concepts from the multitude of different translation studies areas listed in Baker (1998a), the “Bibliography of Translation Studies” (1998-), Williams and Chesterman (2002) and the “EST-Directory 2003” are brought together on a single map that revises Holmes’s map (1972). Additional practical advantages for the study of translation studies are pointed out.